2014
DOI: 10.4049/jimmunol.1302623
|View full text |Cite
|
Sign up to set email alerts
|

α-Galactosylceramide but Not Phenyl-Glycolipids Induced NKT Cell Anergy and IL-33–Mediated Myeloid-Derived Suppressor Cell Accumulation via Upregulation of egr2/3

Abstract: Strategies for cancer immunotherapy include activating immune system for therapeutic benefit or blockade of immune checkpoints. To harness innate immunity to fight cancer, a-galactosylceramide (a-GalCer) has been used to activate NKT cells. Unfortunately, administration of a-GalCer causes long-term NKT cell anergy, but the molecular mechanism is unclear. In this study, we showed that a-GalCer-triggered egr2/3, which induced programmed death 1 and cbl-b in NKT cells, leading to NKT cell anergy. We also uncovere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 51 publications
1
48
2
Order By: Relevance
“…NKT cell activation in a mouse model of multiple sclerosis was reported to provide protection via the induction of MDSCs, 44 and administration of free a-GalCer has been shown to increase MDSCs in a hepatotoxicity model. 37 In contrast, NKT cells suppresses MDSC accumulation during viral infection, 29 and activated NKT cells can induce MDSC differentiation into DCs. 29,46,57,58 In expanded memory T cell cultures, an increased number of mouse CD49b C T cells or human CD161 C T cells reduced the suppressive effects of MDSCs, leading to enhanced IFNg production in response to tumor antigens.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…NKT cell activation in a mouse model of multiple sclerosis was reported to provide protection via the induction of MDSCs, 44 and administration of free a-GalCer has been shown to increase MDSCs in a hepatotoxicity model. 37 In contrast, NKT cells suppresses MDSC accumulation during viral infection, 29 and activated NKT cells can induce MDSC differentiation into DCs. 29,46,57,58 In expanded memory T cell cultures, an increased number of mouse CD49b C T cells or human CD161 C T cells reduced the suppressive effects of MDSCs, leading to enhanced IFNg production in response to tumor antigens.…”
Section: Discussionmentioning
confidence: 99%
“…As repeated NKT cell stimulation with free glycolipid is known to induce anergy, [36][37][38] we performed a dose response study using single injections of a-GalCer. A significant increase in overall survival time was observed with the highest dose (i.p.…”
Section: Glycolipid Treatments Reduce Metastasismentioning
confidence: 99%
See 1 more Smart Citation
“…2A, B and 3A, B ). It has been suggested that the ability of an Ag to induce i NKT cell hypo-responsiveness correlates with its antigenic strength (23, 38). However, our data do not support this model.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the list of single factors with direct and indirect influence on the evolution of the immune response continues to grow—particularly small molecule metabolites and the pathways regulating them (e.g. indoleamine dioxygenase [74], arginase [75], and α-galactosylceramide [76]), “danger” pathways (e.g., DAMPs, TLRs, and high-mobility group box-1 release [77], for a review see [78]), and innate immune, wound-healing, and inflammatory signals (e.g. STING pathway ligands, inflammasome expression, TGF-β family signaling, and NFκB induction).…”
Section: Profiling Prediction and Personalization In Immunotherapymentioning
confidence: 99%